Stabilization of the mental state in the perceptions of psychology students - Borodulkina, Tetiana (Psychological Prospects Journal, 2024)
Purpose. Based on the analysis of the results of the theoretical and empirical study, to describe the perceptions of psychology students about mental stabilization in order to further take into account the results obtained in professional training, in particular, in teaching such disciplines as «Crisis Psychology», «Psychological Assistance in Emergency Situations», etc. Methods. Online survey in Google forms; content analysis; frequency analysis; interpretation and generalization of empirical research results. Results. The most frequent words in the respondents’ answers about stabilization of the mental state were: «state»; «mental», «psychological», «psyche», «soul»; «me»; «person», «people»; «stabilization», «stable» / «unstable», «stabilize», «stability»; «emotions», «emotional», «emotionality»; «calm», «calm down», «normal», «normalization», «normalize»; «stress», «stressful» and similar; they were used by the vast majority of respondents when answering the question «How do you understand the expression «stabilization of mental state»?». The content analysis of answers to the question «In what cases does a person need to stabilize their mental state?» revealed that the majority of respondents believe that stabilization of the mental state is necessary in case of disharmony and imbalance of the mental and emotional sphere, stress, deterioration of health; a significant number of respondents consider external factors (traumatic, extreme and emergency events) to be cases in which a person may need mental stabilization. The results of the content analysis of answers to the question «Why should a person stabilize their mental state?» show that a minority of respondents have an active position aimed at changing their mental state, improving it, and achieving results; the majority is focused either on maintaining the current state or avoiding negative consequences. Conclusions. The results of both the theoretical review and the survey draw attention, on the one hand, to the superficiality, stereotypicality, and the presence of various interpretations of the stabilization of mental states by modern researchers, and, on the other hand, to the stereotypicality, formality, and abstractness of future psychologists’ understanding of the stabilization of mental states.